Characteristics And Regimen Modifications In Drug-Sensitive Tuberculosis Patients With Drug-Induced Liver Injury: A Retrospective Study - umi fatma wati; Fahmi Dimas Abdul Aziz; Rasyidin Rumulus; Indah Tripujiati (JURNAL FARMASI DAN MAKANAN, 2026)
Drug-induced liver injury (DILI) is a serious side effect of first-line anti-tuberculosis drugs (isoniazid, rifampicin, pyrazinamide, ethambutol) in drug-sensitive tuberculosis (TB SO) patients, which can lead to treatment interruption and drug resistance. This retrospective observational study aims to analyze the usage patterns in TB SO patients with DILI using patient medical records from January 1 to December 31, 2024. The variables analyzed include demographic characteristics and the ATT regimen. Out of 100 patients, the majority were male (61%), aged 18-59 years (58%), and had a BMI <18.5 kg/m² (68%). All patients (100%) suffered from pulmonary TB; 74% were new cases and 26% had a history of previous treatment. DILI most often occurs in the first month of the intensive phase (74%). Comorbidities were found in 66% of patients (diabetes mellitus 48%, hypertension 18%). A history of smoking was reported in 51% of patients. Management of DILI: 61% underwent modification of the RHZE regimen, 39% experienced temporary cessation followed by reintroduction. The most common non-hepatotoxic regimen was streptomycin-levofloxacin-ethambutol (SLE) in 83% of modified cases. Severe DILI was found in 53% of patients and very severe DILI in 47% of patients. DILI remains a significant challenge in the treatment of SO TB, especially in patients with malnutrition, diabetes mellitus, and a history of smoking. Modification of the regimen and strict monitoring of liver function are crucial to improving clinical outcomes. Keywords: DILI, drug-sensitive tuberculosis, hepatotoxicity, anti-tuberculosis drugs